For better or for worse? Psychosocial work environment and direct participation practices. (July 2019) - Llorens, Clara; Navarro, Albert; Salas, Sergio; Utzet, Mireia; Moncada, Salvador
Highlights: A better psychosocial work environment is associated with direct participation (DP). Low skilled jobs could be designed healthier by using direct participation formulas. Psychosocial work environment is better for women when direct participation is used. Direct participation practices by themselves would not degrade working conditions. DP appears to be a valid component for primary prevention at workplace level. Abstract: Aim: To explore the relationship between the psychosocial work environment and labour management practices involving direct participation among salaried workers; to examine whether this relationship varies according to occupational group and sex. Methods: Based on a representative survey of the wage-earning population in Spain (n = 4911) using the Spanish version of the Copenhagen Psychosocial Questionnaire (COPSOQ-ISTAS21), ordinal logistic models were fitted in order to assess associations. Results: The psychosocial work environment factors control, social support and rewards were significantly and positively associated with direct participation practices, after adjusting for ten indicators of other labour management practices (working hours, contractual relationship, promotion, salary and staffing) and three socioeconomic characteristics (occupational group, sex and age). No association was observed with the factor demands . When used simultaneously, delegative and consultative direct participation practices obtained more frequent and stronger associations with psychosocial work environment factors than when used separately. Stratifying the salaried population by sex and occupational group, associations were observed in all strata except for supervisors and higher professionals. Conclusions: A better psychosocial work environment is associated with direct participation practices among lower level occupational groups and among women. Direct participation practices appear to be valid components of preventive interventions at the workplace level, and may help to reduce occupational health inequalities.